2018
DOI: 10.1016/j.ijheatmasstransfer.2017.09.103
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer and pressure drop in the transitional flow regime for a smooth circular tube with twisted tape inserts and a square-edged inlet

Abstract: HIGHLIGHTS• Experimental investigation of transitional flow regime in tubes with twisted tapes.• Results based on heat transfer coefficients and pressure drops.• Transitional flow regime was influenced by variation in twist ratios.• Variation in heat fluxes influenced the transitional flow regime.• Transition is earlier as the twist ratios and heat fluxes reduced. ABSTRACTThe purpose of this study was to experimentally investigate the heat transfer and pressure drop characteristics in the transitional flow reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 77 publications
(117 reference statements)
10
59
0
2
Order By: Relevance
“…This corresponds to the Chilton-Colburn analogy [3], which was developed for laminar and turbulent flow over flat plates, that shows that there is a direct relationship between friction factor (pressure drop) and Colburn j-factor (heat transfer). Similar findings were also made by Everts [50] and Meyer and Abolarin [26]. However, Tam et al [7] found that the transition region, ΔRe, was wider for heat transfer than for pressure drop.…”
Section: Relationship Between Pressure Drop and Heat Transfersupporting
confidence: 76%
See 2 more Smart Citations
“…This corresponds to the Chilton-Colburn analogy [3], which was developed for laminar and turbulent flow over flat plates, that shows that there is a direct relationship between friction factor (pressure drop) and Colburn j-factor (heat transfer). Similar findings were also made by Everts [50] and Meyer and Abolarin [26]. However, Tam et al [7] found that the transition region, ΔRe, was wider for heat transfer than for pressure drop.…”
Section: Relationship Between Pressure Drop and Heat Transfersupporting
confidence: 76%
“…The results Nu/Pr 0.42 are plotted as a function of (Re -1 000) in Fig. 14(a), and a power curve-fit was done to obtain the following correlation: (26) The method of Churchill and Usagi [52] was used to obtain a single correlation that is valid for all four flow regimes: respectively, in terms of the modified Grashof number. Table 2 summarises the valid ranges and performances of the average friction factor and average Nusselt number correlations for developing and fully developed flow, which were developed in this study.…”
Section: Average Nusselt Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found from analysing the experimental data of this study and literature [41,44], that all mixed convection data in the laminar and transitional flow regimes could be represented as shown schematically in Fig. 5.…”
Section: Heat Transfer Regions For Laminar and Transitional Flowmentioning
confidence: 66%
“…The transitional flow regime itself has also been extensively investigated by Ghajar and co-workers [27][28][29][30][31][32][33][34][35][36] as well as Meyer and co-workers [37][38][39][40][41][42][43][44], however, the focus of these studies were on the effects on inlet geometries, enhanced tubes, nanofluids, micro-channels, annuli and twisted tape inserts. While Ghajar and co-workers considered mainly fully developed flow, Meyer and co-workers used the average measurement across a tube length.…”
Section: Introductionmentioning
confidence: 99%